2010
DOI: 10.1161/atvbaha.110.209643
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of the Thioredoxin System in Angiogenesis

Abstract: Notwithstanding a multitude of studies, the mechanisms of angiogenesis remain incompletely understood. Increasing evidence suggests that cellular redox homeostasis is an important regulator of angiogenesis. The thioredoxin (TRX) system functions as an endogenous antioxidant that can exert influence over endothelial cell (EC) function via modulation of cellular redox status. It has become apparent that the cytosolic thioredoxin-1 (TRX1) isoform participates in both canonical and novel angiogenic signaling pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
81
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 135 publications
(138 reference statements)
1
81
0
1
Order By: Relevance
“…Other studies showed that enhanced TRX can increase VEGF expression (17,19,31,50), which can account for the observation of similar VEGF levels in TKO and WT animals. These findings clearly suggest that impaired VEGF angiogenic response in this model is likely due to its impaired signaling rather than levels of VEGF.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Other studies showed that enhanced TRX can increase VEGF expression (17,19,31,50), which can account for the observation of similar VEGF levels in TKO and WT animals. These findings clearly suggest that impaired VEGF angiogenic response in this model is likely due to its impaired signaling rather than levels of VEGF.…”
mentioning
confidence: 89%
“…The crosstalk between the two systems, as indicated by the ratio of the oxidized to reduced glutathione (GSSG/GSH) reflects antioxidant capacity of the cell (18,19). Shifting redox state to more GSSG reflects a state of oxidative stress, while shifting to more GSH reflects a state of reductive stress.…”
Section: Introductionmentioning
confidence: 99%
“…Trx affects cell growth and proliferation via regulating the redox status in cells (5). Trx-1 is also implicated in cell survival, tumor development and angiogenesis (6,7). Numerous studies demonstrated that overexpression of Trx is observed in many cancers such as gastric and breast cancers (5,8).…”
Section: Introductionmentioning
confidence: 99%
“…However, Trx2 was down-regulated by MMC in MTEC1 cells and showed no long-lasting change in MTEC1 cells that were treated with MMC plus Dox. It has been shown that Trx2 can inhibit cell apoptosis via inhibition of the ASK1/JNK signaling pathway [42]. In conclusion, Dox protects TECs from apoptosis via the NF-κB-Bcl-2/Bax and Trx2-ASK1/JNK signaling pathways and may serve as a novel reagent for the treatment of thymic atrophy.…”
Section: Discussionmentioning
confidence: 89%